Molecular Phylogenetics of Dominant Endophytic Fungi in Leaves of Vitellaria paradoxa using Internal Transcribed Spacer gene region - Lateef, Adebola; AbdulMalik, AbdulKabir Omeiza; Mustapha, Fareedah Toyin; Tiamiyu, Bashir Bolaji; Ajijolakewu, Kamoldeen Abiodun (Journal of Science and Technology, 2025)
On a global scale, diverse fungal species live inside plant tissues in mutualistic association either as highly specific to single hosts or widespread in many species. Despite the huge importance of Vitellaria paradoxa (Shea Butter Tree) in Africa, the fungal endophytes associated with this plant have not been documented. In this study, we characterized and determined the phylogenetic relationship of the endophytic fungi in V. paradoxa. Fungal isolation was done from V. paradoxa between July and December, 2019 by cutting, sterilizing and inoculating the healthy leaves on Potato Dextrose Agar (PDA) and Water Agar (WA) for 7 and 21 days respectively. Result of the isolation showed a dominant fungal endophyte repeatedly isolated from the leaves of V. paradoxa. Morphological features of the isolates were described and the genomic DNA was extracted for molecular analyses. Accurate molecular phylogenetic analyses of the sequences of the Internal Transcribed Spacer (ITS) gene regions using maximum likelihood analysis revealed the isolate as Lasiodiplodia theobromae. This study therefore succinctly represents the first report of L. theobromae as an endophyte in leaves of V. paradoxa using a robust analysis of its phylogeny. The implication of the occurrence of this endophytic fungus from shea butter fruit is also discussed.